Present-Focused Preferences and Sin Goods Consumption at the Extensive and Intensive Margins - Zarko Kalamov; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper analyzes sin goods consumption when individuals exhibit present-focused preferences. It considers three types of present focus: present-bias with varying degrees of naiveté, Gul-Pesendorfer preferences, and a dual-self approach. We investigate the incentives to deviate from healthy consumption (the extensive margin). In the first model, the extensive margin of consumption is independent of the degree of present-bias and naiveté. Likewise, in the latter frameworks, the strength of temptation and the cost of self-control do not affect the extensive margin. Hence, present-focused preferences affect the intensive margin of sin goods consumption, but not the extensive margin.
Keywords: D11; D15; D60; D91; I12; 330; present-bias; self-control; temptation; dual-self; sin goods